Psychopathic traits are associated with reduced attention to the eyes of emotional faces among adult male non-offenders - Gillespie, Steven M.; Rotshtein, Pia; Wells, Laura J.; Beech, Anthony R.; Mitchell, Ian J. (Frontiers in Human Neuroscience, 2015)
Psychopathic traits are linked with impairments in emotional facial expression recognition. These impairments may, in part, reflect reduced attention to the eyes of emotional faces. Although reduced attention to the eyes has been noted among children with conduct problems and callous-unemotional traits, similar findings are yet to be found in relation to psychopathic traits among adult male participants. Here we investigated the relationship of primary (selfish, uncaring) and secondary (impulsive, antisocial) psychopathic traits with attention to the eyes among adult male non-offenders during an emotion recognition task. We measured the number of fixations, and overall dwell time, on the eyes and the mouth of male and female faces showing the six basic emotions at varying levels of intensity. We found no relationship of primary or secondary psychopathic traits with recognition accuracy. However, primary psychopathic traits were associated with a reduced number of fixations, and lower overall dwell time, on the eyes relative to the mouth across expressions, intensity, and sex. Furthermore, the relationship of primary psychopathic traits with attention to the eyes of angry and fearful faces was influenced by the sex and intensity of the expression. We also showed that a greater number of fixations on the eyes, relative to the mouth, was associated with increased accuracy for angry and fearful expression recognition. These results are the first to show effects of psychopathic traits on attention to the eyes of emotional faces in an adult male sample, and may support amygdala based accounts of psychopathy. These findings may also have methodological implications for clinical studies of emotion recognition.